Reconstructing Maslahah as an Epistemological Principle within the Framework of Religious Liberalism: Toward a New Rationality in Usul al-Fiqh - Zulfan Efendi; Rahmat Efendy Al Amin Siregar (Hukum Keluarga Islam IAIN LANGSA, 2026)
Most research on maslahah stops only on methodological instruments in legal istinbat and research on liberalism is only centered on theological and political frameworks, without systematically reconstructing the position of maslahah as an epistemological principle in the construction of usul al-fiqh. This research aims to reconstruct the concept of maslahah in the framework of religious liberalism and affirm its position in the epistemology of Islamic law as the basis for the formation of a new rationality in usul al-fiqh. This research is a normative-conceptual research with an approach to Islamic legal theory and legal philosophy, using a literature analysis method on the thoughts of Islamic legal reformers. The main findings of this study show three main things. First, maslahah in the perspective of religious liberalism is positioned as an epistemological principle, not merely an additional methodological consideration. Second, the reconstruction shifts the orientation of usul al-fiqh from a textual-formal approach to a rational-contextual approach that is dialogical between revelation and social reality. Third, the implication is the affirmation of Islamic law as a normative system as well as an ethical-social instrument to realize justice, freedom, and universal welfare (al maslahah al ammah). The implications of this study confirm the need to reorient contemporary Islamic legal methodology towards a more integrative and contextual epistemological paradigm, thereby strengthening the contribution of usul al-fiqh in the discourse of Islamic law reform as well as the development of Islamic legal theories that are responsive to modern social dynamics.